(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
Type 2 diabetes mellitus (T2DM) is associated with various systemic complications, including an increased risk of periodontal disease. This article investigates the immunological and microbiological mechanisms underlying periodontal deterioration in patients with T2DM. The analysis highlights the impact of chronic hyperglycemia on host immune response, microbial dysbiosis, and periodontal tissue destruction. Additionally, it examines the clinical and laboratory correlations that may inform preventive and therapeutic strategies.